Changes in the immigrant Russian-speaking family language policy during the war in Ukraine - Protassova, Ekaterina; Yelenevskaya, Maria (Frontiers in Psychology, 2024)
Introduction The Russia’s full-scale invasion of Ukraine had a significant impact on the Russian-speaking identity, reformulating existing linguistic and cultural boundaries and shaping Russian speakers’ self-perception and vision of the world. We focus on families with children who are trying to balance their inner and outer life in order to stabilize the positive environment of the upbringing process and analyze how adults explain to the children the need to learn the Russian, Ukrainian and other languages. This can shed light on the challenges and strategies employed in alleviating prejudiced attitudes against immigrants’ languages and cultures which can cause alienation from the roots in the one-and-a-half and second generation. The research questions were: How has the war altered language policies in families with different ethnic backgrounds? What changes in home language use strategies do parents propose? Material and methods Material drawn from numerous posts of Facebook discussions have been analyzed with the help of thematic analysis. Results and discussion We observe that in many multilingual families with Ukrainian roots the war has led to a greater emphasis on the Ukrainian language use as an attempt to reinforce ties to their cultural heritage and express support for the country. Russian is increasingly viewed as the language of the aggressor; moreover, Russian culture is devalued and rejected. Some families have become more open to new language learning, especially the languages of their new environment, and try to identify themselves as multicultural and multiethnic personalities. On the other hand, in those families where parents work or study in the fields in which Russian is widely used, adults prioritize the development of Russian language skills in their children in order to improve their future educational and professional opportunities. We explore attitudes and challenges faced by parents in Russian-speaking families, as they demonstrate the complexities of identity formation and language transmission while making salient the interplay between parents’ personal experiences, their aspirations for their children’s cultural identity, and the pressures of integration into the local society.